Big Data Analytics in Health Care System - Vijayalakshmi, M; Kanagasankari, S (International Journal of Computer Sciences and Engineering, 2025)
In Health Sector real time decision making can save a person‘s life. To treat the patient who has disease the doctor needs to know the history [both family and medical] of the patient. Timely decision making is very much important to increase the quality of health care.The patient details are scattered among various stake holders [doctor, scan center, Insurance, medical store] of health industry. Availability of patient data at one place can help the doctors to make diagnosis of disease easily. At the time of emergency doctors need not repeat lab test. Accumulation of patient details at one place which is collected from various resources must be stored in the format for analysis and the data extractedfor effective decision making. The accumulated data can be dealt with big data tools and techniques.The application of Big Data Analytics in Health Care helps to lower health service costs while improving patient care process. This paper deals with the dimensions of Big Data, Tools and Techniques of big data and a Model for Health Care using Big Data.